The role of rural women in building an agri-food system that is fair, healthy, and resilient. - Vega, Gerardo Cerdas (2023)
Interview with Fanny Reyes Ortiz, member of the Rural Women's Network and indigenous leader of the Térraba people, Costa Rica.